2004
DOI: 10.1002/uog.1019
|View full text |Cite
|
Sign up to set email alerts
|

The interobserver reliability of three‐dimensional power Doppler data acquisition within the female pelvis

Abstract: Objectives To examine the interobserver reliability of three-dimensional (3D)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
50
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(51 citation statements)
references
References 18 publications
1
50
0
Order By: Relevance
“…Only an experienced sonologist could acquire the volumes of interest, whereas other sonologists less experienced would be able to process them offline with completely reliable results. Raine-Fenning et al 6,7 also showed high intraobserver and interobserver reproducibility of ovarian 3D-PDA indices. The Intra-CC and, particularly, Inter-CC were not as high as those of Jarvela et al 5 These authors observed an FI Inter-CC of just 0.29 in 22 ovaries after 8 days with controlled stimulation treatment.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Only an experienced sonologist could acquire the volumes of interest, whereas other sonologists less experienced would be able to process them offline with completely reliable results. Raine-Fenning et al 6,7 also showed high intraobserver and interobserver reproducibility of ovarian 3D-PDA indices. The Intra-CC and, particularly, Inter-CC were not as high as those of Jarvela et al 5 These authors observed an FI Inter-CC of just 0.29 in 22 ovaries after 8 days with controlled stimulation treatment.…”
Section: Discussionmentioning
confidence: 90%
“…That means there was no overlap between CIs, which means that the highest CI of a CC was lower than the lowest CI of another CC. 7,19 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations